An overview of growth hormone therapy in pediatric cases documented in the Kabi International Growth Study (Pfizer International Growth Database) - Mitchell E. Geffner; Michael B. Ranke; Michael P. Wajnrajch; for the Pfizer International Growth Database Strategic Executive Committee, Strategic Advisory Board, and International Board (Korean Society of Pediatric Endocrinology, 2024)
The Kabi International Growth Study (KIGS) was first established in 1987 and is the largest pharmaco-epidemiological study of recombinant human growth hormone (rhGH). KIGS is aimed at evaluating long-term safety and treatment outcomes in pediatric subjects who received Genotropin rhGH therapy (Pfizer, New York, NY, USA) as prescribed by physicians in real-world clinical practice settings. KIGS data have been used to answer multiple research questions related to growth, growth prediction, and growth hormone treatment, leading to the publication of 129 peer-reviewed manuscripts and 24 biannual reports, outcomes from 10 expert meetings, and 3 books. The KIGS has shown that rhGH is safe and increases both the short-term height gain and adult height in patients with GH deficiency (GHD) and multiple other non-GHD conditions associated with short stature.